EDUCATING HEALTH PROFESSIONALS: BECOMING A UNIVERSITY TEACHER
XII, 339 p.
Keywords: This book is for health professionals who are becoming involved in the education of people entering their professions. It introduces many of the challenges that educators must engage with in the twenty-first century; challenges that will preoccupy our attention for many years to come. The world of professional practice in healthcare is changing and the education we provide to prepare people for that practice is also changing. How do we prepare professional practitioners for this changing world? How do we prepare them for the changes that are yet to come? What challenges and changes do they need to be aware of? How do we prepare educators – both academics and workplace educators for these challenges? This volume opens up and articulates the issues we face in preparing people to enter the contemporary world of healthcare. Experienced educators should also find much of interest in these pages. Practice-based education provides an overarching framework for consideration of the issues involved. There are five sections in the book: - Section 1: Introduction - Section 2: Health Professional Education in Context - Section 3: Teaching and Research - Section 4: Case Studies - Section 5: Future Directions.